Meningkatkan Hasil Belajar Siswa dengan Pengembangan Media Pembelajaran E-Learning Berbasis Blog - Devita Mustika Weni; Gatot Isnani (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2016)
Abstract: The purpose of this research is: (1) produce Blog-based E-learning instructional media, (2) measure the students’ learning outcomes after utilizing Blog-based E-learning instructional media; and (3) to determine differences in students’ learning outcomes both in the control class and experimental class. This research and development has been conducted by using the R & D model developed by Sugiyono, through these following steps: (1) the potential and problems, (2) data collection, (3) the design of the product, (4) design of the validation, (5) a revised design, (6) test products, (7) product revision, (8) utility testing, (9) the revision of the product, and (10) the produced product. The subject of this research on the Tenth Grade Students of Office Administration at SMKN 1 Turen Malang. Based on research result, the average posttest score from the experimental class is 95.61 and control class is 88.28 which show that there is difference between the posttest score for experimental class with the control class. Based on the comparison of the posttest score, Blog-based E-learning instructional media that has been developed can improve learning outcomes of students in the experimental class.Abstrak: Tujuan penelitian ini adalah: (1) menghasilkan media pembelajaran E-learning berbasis Blog, (2) mengukur hasil belajar siswa setelah menggunakan media pembelajaran E-learning berbasis Blog, (3) untuk mengetahui perbedaan hasil belajar siswa pada kelas kontrol dan kelas eksperimen. Penelitian pengembangan ini dilakukan dengan menggunakan model pengembangan Research and Development yang dikembangan oleh Sugiyono, melalui tahap-tahap: (1) potensi dan masalah, (2) pengumpulan data, (3) desain produk, (4) validasi desain, (5) revisi desain, (6) uji coba produk, (7) revisi produk, (8) uji coba pemakaian, (9) revisi produk, dan (10) produk yang dihasilkan. Sasaran penelitian ini adalah siswa kelas X Program Keahlian Administrasi Perkantoran SMKN 1 Turen. Berdasarkan hasil analisis data, rata-rata nilai posttest kelas eksperimen 95,61 dan kelas kontrol 88,28 menunjukkan bahwa adanya perbedaan nilai posttest antara kelas eksperimen dengan kelas kontrol. Berdasarkan perbandingan nilai posttest tersebut, maka media pembelajaran E-learning berbasis Blog yang dikembangkan dapat meningkatkan hasil belajar siswa pada kelas eksperimen.